Role of Plant Diagnostic Laboratory for Identification and Management of Insect Pests of Paddy in Kapurthala District - Singh, Gurmeet; Sharma, Manoj; Manan, Jatinder; Singh, Gobinder (Journal of Agricultural Extension Management, 2018)
Paddy is grown under different agro-climatic conditions and the crop isdamaged by more than 100 species of insect pests and infested by varieddiseases. These insect pests cause enormous grain yield losses, which may varyfrom 20 to 50 per cent if not managed in time. During the last 3 years i.e. from2013 to 2015, a record of all the visiting farmers was maintained in the planthealth diagnostic laboratory at the Krishi Vigyan Kendra, in which completedetails of the farmer with address and contact number was maintained. It wasnoticed that majority of the farmers (80.5%) visited during the month of Apriland only 19.5 per cent visited in the month of May as sowing of paddy nurserystarts from the first week of May every year. The crop was also found to beprone to micro nutrient deficiency and showed deficiency symptoms in ironand zinc. It was inferred that before the sowing and harvesting of the crop, thefarmers queries were maximum due to the fact that majority of insect pest attackÂ takes place near maturity of the crop which results in huge loss, if not taken seriously. As Krishi Vigyan Kendra imparts short duration training to farmers from time to time, it can be concluded that KVK staff should provide trainingÂ relating to the above mentioned technological problems in a particular month.